(untitled) (Journal of University of Babylon for Engineering Sciences, 2022)
This paper proposes a new detection algorithm with better performance for spatial modulation (SM) systems, which uses (M-PSK) or (M-QAM) constellation diagram. The proposed algorithm has enhanced to M-algorithm-based maximum likelihood detector (M-ML). Mathematically, we analyzed the number of mathematical discussions of the ML detector which determining from (M-ML) algorithm on the first receiving antenna down to the last receiving antenna. Then counting the smallest value for these mathematical discussions at each receiving antenna, which refers to both the received symbols and the number of the effective antenna on the transmitter side. The proposed algorithm named (L-ML). The simulation results showed that the proposed algorithm gave an improvement in bit error rate (BER) value compared with the algorithm (M-ML). Both algorithms (M-ML) and (L-ML) have the same value of computational complexity. The results of the proposed algorithm (L-ML) were verified by simulation with Matlab.